Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan Yang Terdaftar di Bursa Efek Indonesia - Cindy Hwang; Vargo Christian Christian L. Tobing (eCo-Buss, 2022)
The research is to find out the effect of good corporate governance such as the size of the board of commissioners, institutional ownership, and managerial ownership to company’s performance such as by Return of Equity (ROE) in the properties and real estate sector companies that listed on the Indonesia Stock Exchange from 2016-2020. The sampling technique used in this study is purposive sampling technique where the total samples used in this study are 7 companies and financial reports for 5 years. The data used in this study is secondary data in the form of the company's annual financial statements obtained from the Indonesia Stock Exchange website. The results of this study show that the board of commissioners' size variables have an effect significant on company’s performance (ROE). Institutional ownership and managerial ownership has no effect significant on return on equity. The size of the board of commissioners, institutional ownership and managerial ownership have an effect significant on return on equity. The coefficient of Determination (R2) indicates that the dependent variable is influenced indenpendent variables in this study by 24.8% and the remaining 75.2% is influenced by other factors that are not included in this study